2016
DOI: 10.1016/j.nbd.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Subthalamic local field potentials in Parkinson's disease and isolated dystonia: An evaluation of potential biomarkers

Abstract: Local field potentials (LFP) recorded from the subthalamic nucleus in patients with Parkinson’s disease (PD) demonstrate prominent oscillations in the beta (13–30 Hz) frequency range, and reduction of beta band spectral power by levodopa and deep brain stimulation (DBS) is correlated with motor symptom improvement. Several features of beta activity have been theorized to be specific biomarkers of the parkinsonian state, though these have rarely been studied in non-parkinsonian conditions. To compare resting st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 60 publications
3
79
1
Order By: Relevance
“…Despite being common across nodes, β-HFO PAC in the current analysis seems to carry little clinical significance, not correlating with symptom severity. Furthermore, β-HFO PAC is present in dystonia patients in both STN (Wang et al, 2016) and GPi, (in the current report). Given the lack of clinical correlation and its presence across diseases, more work is needed to define whether β-HFO PAC is still valuable as a specific biomarker of PD.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Despite being common across nodes, β-HFO PAC in the current analysis seems to carry little clinical significance, not correlating with symptom severity. Furthermore, β-HFO PAC is present in dystonia patients in both STN (Wang et al, 2016) and GPi, (in the current report). Given the lack of clinical correlation and its presence across diseases, more work is needed to define whether β-HFO PAC is still valuable as a specific biomarker of PD.…”
Section: Discussionsupporting
confidence: 71%
“…Recent reports in the literature suggest that coupling and not merely the power of β oscillations may be an important underpinning of PD pathophysiology (de Hemptinne et al, 2015; Swann et al, 2015; Wang et al, 2016). So far, the literature has been largely focused on analysis of STN and motor cortical LFPs.…”
Section: Discussionmentioning
confidence: 99%
“…Crucially, our results demonstrate a spectrally highly focal association of peak theta activity with clinical symptom severity in a large cohort of cervical dystonia patients. 38 Given our findings on pallidal coherence and the previously described presence of theta activity in the subthalamic nucleus in dystonia patients, [11][12][13] we hypothesize that subcortical theta synchronization may represent a "noisy signal" as proposed by Marsden and Obeso 39 in the cortex-basal ganglia-thalamic loop that may interfere with physiological motor network function, leading to the generation of dystonic muscle contractions. 18 Both neuroimaging and electrophysiological studies have revealed structural and functional network changes in dystonic patients that have resulted in the current opinion that dystonia is a circuit disorder.…”
Section: Role Of Pallidal Theta Activity In the Pathophysiology Of Dymentioning
confidence: 52%
“…20 Before spectral analysis, all data segments with artifacts were rejected after visual inspection. Nine contact pairs from 5 patients (Cases 8, 10,13,14,15) had to be excluded from all analysis because of continuous contamination by artifacts. Nine contact pairs from 5 patients (Cases 8, 10,13,14,15) had to be excluded from all analysis because of continuous contamination by artifacts.…”
Section: Spectral Analysismentioning
confidence: 99%
“…We also calculated the height of the beta peak normalized to baseline power using a previously described method 37 . In brief, the log of the PSD was taken and fit to a 5 th order polynomial to approximately remove the 1/f component of the PSD 25 .…”
Section: Methodsmentioning
confidence: 99%